Eco-Innovation: Applying the Woven Fabric from Dendrocalamus asper Fibers to Textile Product Design - Cholthicha Sarikanon; Thanate Piromgarn; Sirisyos Kijmongkolvanich; Songwut Egwutvongsa (International Journal of Sustainable Development and Planning, 2025)
The objectives of this research were 1) to test the properties of the woven fabric from Dendrocalamus asper (D.asper) fiber blended with recycled polyester(r-PET), and 2) to study the design factors and evaluate the satisfaction with the new textile products.This is a mixed method research study, the results of which indicated that the physical properties of the developed textile fabric were assessed in accordance with textile testing standards, tensile strength, tear strength, fabric density, fabric weight, fabric thickness, abrasion resistance, and pilling resistance.The obtained fabric contained the unique textures of D.asper fiber blended with recycled polyester fibers.The population consisted of 3,012 visitors to Crafts Bangkok 2024 Thailand.The sample consisted of 353 visitors to Crafts Bangkok 2024 Thailand with an interest in textile products, obtained by simple random sampling with a 95% confidence level.Structured questionnaires with good quality (Cronbach's alpha = 0.919) were used as the research instrument.According to the exploratory factor analysis (EFA), there were four factors affecting consumers, i.e., 1) local materials, 2) green products, 3) healthiness, and 4) sustainability.Consumers had high levels of satisfaction with the new textile products (x = 4.235; S.D = 0.472).All four factors significantly affected consumer satisfaction (p < .01)and could predict the dependent variable at 84.7%, with the standardized regression equation: = .196( 1 ) + .394( 2 ) + .244( 3 ) + .307( 4 ).The new textile products can therefore encourage the use of the abundantly available bamboo fibers in communities through sustainable development that helps increase economic value with eco-friendly qualities.
Keywords: Crafts, Textile, and Design